Incidence of fractures in people with intellectual disabilities over the life course: a retrospective matched cohort study - Frighi, V; Smith, M; Andrews, TM; Clifton, L; Collins, GS; Fuller, A; Roast, J; Holt, TA (Elsevier, 2022)
Background: Current osteoporosis guidelines do not identify individuals with intellectual disabilities (ID) as at risk of fracture, potentially missing opportunities for prevention. We aimed to assess the incidence of fractures in people with ID over the life course.